Four-wave-mixing-assisted brillouin fiber laser with double-brillouin-frequency spacing - Gan, G.K.W.; Yeo, K.S.; Adikan, Faisal Rafiq Mahamd; Shee, Yu Gang (Elsevier, 2015)
The generation of multiwavelength Brillouin fiber laser assisted by four wave mixing has been demonstrated. A maximum of 18 channels of laser Stokes lines are generated at a Brillouin Pump (BP) of 190 mW (similar to 22.5 dBm). The multiple peaks have a wavelength spacing of 0.176 nm (similar to 20 GHz). A tunable optical bandpass filter is incorporated to the design to suppress up to 6 dB of the noise floor hump exhibited at the multiwavelength laser spectrum while limiting the laser peaks attenuation thereby providing a much cleaner and better OSNR. (C) 2014 Elsevier Inc. All rights reserved.